For Loan Processing a Fuzzy Process Mining - İbrahim Ethem Yazıcı; Orhan Engin (Journal of Advanced Research in Natural and Applied Sciences)
Process mining has been used extensively in recent years to develop the steps of the business and it is an important technique to remove waste and reduce process costs. The aims of this study indicate congestion, workflow which lived a long time, and stuff or system statistics in the banking real estate transaction process. The process mining practice is applied in bank business loans. In the bank process, the most used and complicated business is a bank loan transaction. The process mining implementation pattern is created with sample and flow gains of process development. Then, the new workflow is designed and the pattern is executed. In the first stage of the total loan period, 7.84 hours of earnings are obtained. Visualizations of the process have been affected with the help of fuzzy model algorithms necessary for a huge number of incidents and activities. Workflow analysis and gathering information for studies were to be effortless with the support of fuzzy models. As a result of the analysis based on the flows, the knowledge pool is created by getting the know-how such as the average duration of the process and the deviations in the users or systems. The results indicated that process mining is a significant methodology for developing bank loan transactions and enhancing their performance.